Assessing the Prospects of the Wine Industry in Kathmandu Valley: An Exploratory Study (Quest Journal of Management and Social Sciences, 2026)
Background: The wine industry in Nepal has been gradually expanding, particularly in urban areas such as Kathmandu Valley. Understanding public awareness and perceptions toward wine businesses is important for the growth and promotion of the beverage industry in Nepal.Purpose: This research work was carried out to access the prospects of Wine business in Kathmandu Valley. To promote and enhance the beverage industries in Nepal it is very important to find out the possible challenges and outcome.  The major objective of this study was to find out the general understanding of wine business in Kathmandu valley.Design/methodology /approach: The exploratory research design was adopted, and data was collected using structured questionnaires. Both descriptive and inferential analyses were used where STATA was used for inferential analysis. Kathmandu valley residents were taken as a population, and 403 individuals were taken as a sample. The study has used the non-probability sampling technique. The base theory of the research is Findings: The study conducted shows that majority of the respondents are aware and have knowledge about Wine Business in Kathmandu Valley. People tend to know about wine and its benefits and makings. Result of STATA method shows that 11 variables used in the study are significant. Conclusion: The goal of the study was to know the awareness of people in wine business in Kathmandu Valley, as well as to provide insight into various perspectives and variables. The primary goal of the study is the factors determining the wine business in Kathmandu valley. Based on conclusion this study recommended increased awareness level of people residing in Kathmandu there are various things that should be carried out by the government and the companies that manufacture wine. Keywords: Wine Business, Alcohol, Beverage, Kathmandu Valley, Awareness Index